The Potential of Talisay-Dagat (Terminalia catappa L.) for Phytoremediation in Langihan Lagoon, Butuan City, Agusan del Norte, Philippines - Magcuro, Christian Granzon; Mangubat, Chaly Benson; Sullano, Allysa Concepcion Alba; Corbita, Victor Lobrigas; Mercado, Joel Andig; Casilac Jr., Cornelio Sacquiap (Department of Forestry, Faculty of Agriculture, University of Lampung, 2024)
The study aims to determine the potential of Talisay-dagat (Terminalia catappa L.) for phytoremediation and to examine its influence on reducing concentrations of heavy metals in the soil of Langihan Lagoon, Butuan City. Soil, roots, and leaves were collected and brought to the Regional Soils Laboratory using microwave-assisted aqua-regia digestion and determination through Inductively Coupled Plasma Optical Emission Spectrometer. The study made use of mathematical computations such as translocation factor (TF), bioconcentration factor (BCF), and enrichment factor (EF) to determine whether the tree is a hyperaccumulator, excluder, or indicator. In the TF results, T. catappa was a hyperaccumulator for Ni and Cu, considering that the concentration exceeds one (1) while demonstrating as a possible excluder for Cr. There was also an emphasis on limited absorption of heavy metals, as evidenced by the BCF and EF value of less than 1. The results show that based on TF, BCF, and EF values, only TF shows the effectivity of restricting the root-shoot ratio translocation of Ni and Cu (TF > 1). Regression analysis found that the absorption of T. catappa was not influenced by the amount of heavy metal in the soil within the studied condition. This insight was crucial in understanding the plant’s absorption and could guide further research or practical applications in environmental management and phytoremediation. Keywords: bioconcentration factor, hyperaccumulator, phytoremediation, Terminalia catappa, translocation factor